Frequency of Rhinoplasty Requests During Adolescence: A Single-Center Retrospective Analysis - Simay Erşahin; Ayben Leblebici (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
Globally, many nasal surgeries are performed to address both aesthetic and functional concerns rather than purely functional issues. In recent years, increasing aesthetic awareness among adolescents has led to a growing number of visits to plastic surgery clinics for rhinoplasty requests. This study aimed to retrospectively evaluate rhinoplasty requests in a state hospital setting, with particular attention to adolescent applicants and the functional nasal findings associated with surgical decision-making in this age group. During the 18-month study period, 867 patients presented to the Plastic, Reconstructive, and Aesthetic Surgery Clinic with a request for rhinoplasty. Patients were categorized as adolescents (≤19 years) and adults (≥20 years). Demographic data, surgical status, and functional nasal findings, including significant axis deviation, septal deviation, breathing difficulty, and concha hypertrophy, were analyzed. Rhinoplasty was performed in 88 patients, including 82 adults and 6 adolescents. Among adolescents who underwent surgery, functional nasal findings were prominent, most commonly septal deviation accompanied by breathing difficulty and significant axis deviation. Exploratory comparisons showed that these findings were more frequent in adolescents than in adults, whereas concha hypertrophy did not differ significantly between groups. However, because of the small number of adolescents who underwent surgery, these comparative findings should be interpreted cautiously. Although the surgical rate among adolescent applicants was low, functional problems were prominent among those selected for surgery and frequently accompanied aesthetic concerns. These findings suggest that adolescent rhinoplasty requests should be evaluated through a multidimensional approach considering both functional and aesthetic factors.